The ‘fishnet approach’ to livelihood improvement in depressed basins: Evidence from BRAC’s Integrated Development Programme - Ara, Jinnat; Shahed, Syeda Sitwat; Rahman, Rehnuma; Ahmad, Sibbir (Taylor & Francis, 2022)
This article was published in Development and Practice [©2020 Rights managed by Taylor & Francis and the definite version is available at: https://doi.org/10.1080/09614524.2020.1719978 The Article's website is at: https://www.tandfonline.com/doi/full/10.1080/09614524.2020.1719978